ANALISIS RASIO ROA DAN ROE DALAM MENILAI TINGKAT KESEHATAN PADA PT BANK MANDIRI (PERSERO) TBK TAHUN 2012 – 2017 - Timan, Su (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2019)
The purpose of this paper is to find out and analyze the level of health of the Return on Assets (ROA) ratio of PT Bank Mandiri (Persero) Tbk in 2012-2017, to find out and analyze the level of health Return on Equity (ROE) ratio at PT Bank Mandiri (Persero ) Tbk in 2012-2017, to know and analyze the financial performance of PT Bank Mandiri (Persero) Tbk based on the Return on Assets (ROA) ratio and the Return on Equity (ROE) ratio for 2012-2017. The population used in this study is the financial statements of PT Bank Mandiri (Persero) Tbk and its accounts in the form of balance sheets, and income statements of PT Bank Mandiri (Persero) Tbk and subsidiaries from 2012 to 2017 obtained from the official website of PT Bank Mandiri (Persero) Tbk namely http://www.Mandiri.co.id and the Financial Services Authority, namely https://ojk.go.id.The data collection method used in this study is secondary data, with techniques used in the Library (Library Research), Documentation, Internet Research. This research uses descriptive and quantitative analysis methods. In the calculation of Return on Assets (ROA) at PT Bank Mandiri (Persero) Tbk, indicates that the condition of a